Subtle Morphological Changes in the Mandible of Tabby Mice Revealed by Micro-CT Imaging and Elliptical Fourier Quantification - Bornert, Fabien; Choquet, Philippe; Gros, Catherine I.; Aubertin, GaElle; Perrin-Schmitt, Fabienne; Clauss, François; Lesot, Hervé; Constantinesco, André; Schmittbuhl, Matthieu (Frontiers in Physiology, 2011)
X-linked hypohidrotic ectodermal dysplasia (XLHED) is a genetic disorder due to a mutation of Eda gene and mainly characterized by an absence or deficient function of hair, teeth and sweat glands, and craniofacial dysmorphologies. Although the tooth abnormalities in Tabby mutant mice -the murine model of XLHED- have been extensively studied, the characterization of the craniofacial complex, and especially the mandibular morphology has received less attention. From 3D microCT reconstructions of the left mandible, the mandibular outline, in lateral view, was quantified using 2D elliptical Fourier analysis. Comparisons between Tabby specimens and their wild type controls were carried out showing significant shape differences between the mouse strains enabling a clear distinction between hemizygous Tabby specimens and the other mouse groups (WT and heterozygous EdaTa/+ specimens). Morphological differences associated to HED correspond not only to global mandibular features (restrained development of that bone along dorsoventral axis), but subtle aspects (marked backward projection of the coronoid process and narrower neck of the mandibular condyle), providing, for the first time, evidences of a predominant effect of the Ta mutation on the mandibular morphology. Such result parallels the well described abnormalities of jugal tooth row and skeletal defects in Ta mice, underlining the role of EDA-A in the reciprocal epithelial-mesenchymal interactions that are of critical importance in the normal dental and craniofacial development.